Legal Compliance and the Implications of Technological Evolution on Human Resource Management Strategies - Ur-Rahman, Dr. Sami; Akhtar, Noreen; Tabassam, Aliza (Al-Amīr Research Journal for Islamic Studies, 2024)
The legal compliance and the technological changes that have seen the company embrace digitization and automation have greatly influenced how organizations conduct their operations. Artificial intelligence systems, big data, and collaborative working platforms have altered workflows and enhanced business productivity. This research investigates how technological advancements affect human resource management decisions and the law. The study, therefore, uses a literature review, which involves a qualitative data collection approach to help achieve a deeper understanding of the problems to be researched between 2000 and 2023. The outcomes show that technological advancement has considerable impacts on HRM and legal issues, especially in the framework of the Indonesian Law No. 13 of 2003 on Manpower. Although technology has played an important role in improving the efficiency and productivity of human resource management, issues have arisen concerning employees’ privacy and data protection, altered work environment, etc. Keywords: Legal Compliance, Technological Evolution, Human Resources